The article 273 of Criminal Code in the sphere of Federal Courts: a reflection about the possibility of penalty's determination under the legal minimum (Revista do Tribunal Regional Federal da 3ª Região, 2011)
This article aims to stimulate the debate and to invite reflection about penalty’s determination under the legal minimum for the crime fixed in the article 273 of Criminal Code. The legal grounds are the judicial review and the analogy in bonam partem.
Keywords: penalty; judicial review; analogy in bonam partem